DWELLING TIME MANAGEMENT - Salahudin Rafi; Budi Purwanto (Institut Transportasi dan Logistik Trisakti, 2016)
Dwelling time is an unfinished classic matter in Indonesia. As a matter of fact, it is a simple thing and is a small part of port management. The research is trying to get the solutions of the matter by using research and development analysis and quantitative method. The important things to do in solving dwelling time are managing the port well, cutting off the complicated bureaucracy, and using one synchronized system for all services.